Local Economic Structure and Industry Development in Germany, 1993-2001 - Uwe Blien; Jens Suedekum (Institute for the Study of Labor (IZA), 2004)
This paper analyses the impact of dynamic MAR- and Jacobs-externalities on local employment growth in Germany between 1993 and 2001. In order to facilitate a comparison between the neighbouring countries we firstly replicate the study of Combes (2000) on local employment growth in France and find very similar results for Germany. Afterwards we formulate an alternative empirical model that is based on a weighted regression approach. With this model we find that Jacobs-externalities matter in manufacturing, whereas MARexternalities are present in advanced service sectors.
Keywords: R11; O40; 330; dynamic externalities; local employment growth; urbanisation and localisation effects; Regionales Wachstum; Beschäftigungseffekt; Lokalisationseffekt; Urbanisierungseffekt; Regionale Entwicklung; Wissenstransfer; Schätzung; Deutschland